2013
DOI: 10.5301/hipint.5000087
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Bone Density and Metal Ions after Metal-On-Metal versus Metal-On-Polyethylene Total Hip Arthroplasty; Short-Term Results

Abstract: Information on periprosthetic acetabular bone density is lacking for metal-on-metal total hip arthroplasties. These bearings use cobalt-chromium instead of titanium acetabular components, which could lead to stress shielding and hence periprosthetic bone loss. Cobalt and chromium ions have detrimental effects on bone. It is unknown whether serum metal ion levels affect bone density clinically. We compared cementless large femoral head (mean 48 mm) metal-on-metal total hip arthroplasties (M2a-Magnum, Biomet) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There were 26 RCTs (30 papers), all of second generation MOM THA, that reported revisions [ 14 17 , 25 40 , 42 , 49 52 ]. These studies comprised 1,546 MOM THA (49 revisions) and 1,746 non-MOM THA (24 revisions).…”
Section: Resultsmentioning
confidence: 99%
“…There were 26 RCTs (30 papers), all of second generation MOM THA, that reported revisions [ 14 17 , 25 40 , 42 , 49 52 ]. These studies comprised 1,546 MOM THA (49 revisions) and 1,746 non-MOM THA (24 revisions).…”
Section: Resultsmentioning
confidence: 99%
“…80 Similarly, the average Cr concentrations were 0.50 ~ 2.50 μg/L and 0.80 ~ 5.10 μg/L, respectively, in the whole blood and serum, as shown by the study. 80 Table 3 [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] presents evidence of increased levels of Co and Cr in the blood of patients with Co-Cr-Mo prostheses. The increased concentration persisted for 72 months, and the concentration of both Co and Cr exhibited two peaks, as observed at 24 months (6.20 μg/L of Co, 4.70 μg/L of Cr) and 60 months (8.42 μg/L of Co, 4.58 μg/L of Cr) following surgery.…”
Section: Metabolism Profiles Of the Prosthetic Metals Elevation Of Me...mentioning
confidence: 99%
“…Specifically, the use of a Metal-on-Metal bearing interface tends to result in higher concentrations of metals in the body compared to the Metal-on-Polyethylene or the Metalon-Ceramics bearings. [63][64][65][66][67][68]74,75,92 Moreover, higher levels of metals are commonly detected when the prosthesis is not functioning optimally. 72,93 Elevation in metallic concentration is more likely to occur when bilateral implantation is performed.…”
Section: Metabolism Profiles Of the Prosthetic Metals Elevation Of Me...mentioning
confidence: 99%
“…Gofton et al [139] reported that titanium was released from modular femoral necks after 1 year, and the difference between the preoperative and postoperative serum Ti levels was almost 10-fold. More recently, Zijlstra et al [140] set up a randomized clinical trial to evaluate periprosthetic acetabular bone density and serum Ti ion levels in MoM THA, compared to MoP THA. Contrary to their hypothesis, acetabular bone density was retained with large head MoM THA, compared to 28 mm MoP THA at one year postoperatively.…”
Section: Hip Implantsmentioning
confidence: 99%